The Advances in the Special Microwave Effects of the Heterogeneous Catalytic Reactions - Li, Hong; Zhang, Chunyu; Pang, Chuanrui; Li, Xingang; Gao, Xin (Frontiers in Chemistry, 2020)
In the present, microwave field has been widely used in chemical processes as an important means of intensification. The heterogeneous catalysts coupling with microwave has been shown to have many advantages, such as high catalytic performance and stability. Our objective is to focus an up-to-date overview concerning the advances in the special microwave effects of the heterogeneous catalytic reactions including special thermal effect, microwave plasma, enhanced active groups and the flexibility of structure. This review systematically states the action mechanism and some practical application of microwave-induced catalytic process. Finally, the potential research directions in the field of microwave-induced catalysis are prospected.